Adjuvant management of locally advanced oral squamous cell carcinoma – real-world challenges and opportunities. Issue 8 (October 2021) - Brooker, R.C.; Hobkirk, A.; Cashman, H.; Sato, T.; Broderick, D.; Wong, H.; Kyzas, P.; Haridass, A.; Sacco, J.J.; Schache, A.G.
Abstract: Patients with locally advanced oral squamous cell cancer (LAOSCC) are treated with adjuvant radiotherapy (RT) or chemoradiotherapy (CRT) following surgical ablation. This depends on the pathological risk factors and aims to reduce the risk of local recurrence and improve survival. Delivery of these aggressive treatments is, however, challenging particularly following major surgery. To inform the adaptations necessary to deliver gold-standard therapy, we aimed to describe real-world delivery of multimodality treatment in LAOSCC, in a UK population with high levels of disease incidence and low socioeconomic status. Patients with LAOSCC (T1-4 N1-3/T3-4 N0) who were treated between October 2014 and October 2016 and had a minimum follow up of 24 months were included. They were identified using the Somerset Cancer Register and data were collected through retrospective case note review. Approval was obtained from the audit departments at the relevant NHS institutions, and data were analysed using IBM SPSS Statistics for Windows version 24 (IBM Corp). The analysis included 129 patients with 82% having an initial performance status (PS) of 0-1. The most frequent change in PS was a one point drop (46%). Twenty of the 93 eligible patients (22%) underwent adjuvant CRT. A total of 37 (40%) began adjuvant CRT/RT within 42 days, and 79 (85%) within 56 days. A delay in initiating adjuvant therapy was associated with higher rates of complications and a longer postoperative hospital stay. Concordance between imaging and pathological nodal staging was poor (cK 0.223). PS frequently declines after complex surgical procedures and long postoperative recovery periods, leading to difficulties providing adjuvant treatments within the national guidance of 42 days. Frequent deviation from planned adjuvant therapies highlights the need for improved treatment strategies.